In Situ Tetraethoxysilane‐Templated Porous Ba0.5Sr0.5Co0.8Fe0.2O3−δ Perovskite for the Oxygen Evolution Reaction. Issue 2 (21st October 2014) - Yang, Yisu; Zhou, Wei; Liu, Ruochen; Li, Mengran; Rufford, Thomas E.; Zhu, Zhonghua
Abstract The perovskite Ba0.5Sr0.5Co0.8Fe0.2O3−δ (BSCF) is one of the best catalysts for the oxygen evolution reaction (OER), which is critical to many energy‐storage applications. However, the catalytic activity of BSCF perovskites is constrained by a low specific surface area (0.5 m2 g−1). We report here, for the first time, a facile, in situ template method using tetraethoxysilane (TEOS) to synthesize porous BSCF with surface areas of up to 32.1 m2 g−1, which to our knowledge is the highest reported surface area in a BSCF perovskite, and with excellent catalytic activity for the OER. For example, the BCSF prepared using a TEOS‐to‐BSCF ratio of 3.4 exhibited up to 35.2 A g−1 at 1.63 V versus a reversible hydrogen electrode (overpotential, η=0.4 V) and this current is 5.3 times that exhibited by nonporous BSCF (6.6 A g−1). The high activity of the porous BCSF is attributed to the additional catalytic surface sites available in the pores created by the in situ TEOS‐template method. The general application of this technique to produce porous perovskites is demonstrated in the synthesis of a second example, porous LaMnO3.